Penguatan Implementasi Manajemen Konflik dan Teknik Asertif dalam Keperawatan di RSU Antonius Pontianak - Cicilia Ika Wulandari; Hany Wihardja (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Conflict is a dispute both internal and external that occurs because of differences in views in an interpersonal relationship. Professional nurse is required to have expertise in conflict management, especially assertive techniques to prevent conflict and deal with conflict effectively. Assertive behavior is the ability to communicate firmly and honestly in an appropriate way so as not to hurt yourself or others. This community service aims to increase the knowledge and skills of nurses in applying conflict management and assertive technique. The implementation method consisted of a survey, PICOT analysis, and a seminar on a group of nurses. This seminar involves 75 nurse participants. The result of data analysis showed that there was an increase in the knowledge of nurses based on pre and post-test. The conclusion of this community service is the importance of practicing assertive techniques on individual nurses as the ability for conflict management in nursing services.